2016
DOI: 10.1177/1533034616657251
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion, Magnetic Resonance Imaging, and Histopathological Findings After Laparoscopic Renal Cryoablation: An In Vivo Pig Model

Abstract: The present study investigates how computed tomography perfusion scans and magnetic resonance imaging correlates with the histopathological alterations in renal tissue after cryoablation. A total of 15 pigs were subjected to laparoscopic-assisted cryoablation on both kidneys. After intervention, each animal was randomized to a postoperative follow-up period of 1, 2, or 4 weeks, after which computed tomography perfusion and magnetic resonance imaging scans were performed. Immediately after imaging, open bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
2
0
2
Order By: Relevance
“…We observed that early changes in BF and BV in advanced RCC patients were of greater magnitude in patients with stable disease compared to progressive disease. While we were unable to demonstrate statistical significance, our result is consistent with preclinical data in which successful anti-angiogenic treatment has been shown to inhibit VEGFR2, decrease tumor vessel number and density based on immunohistochemistry in xenograft and preclinical models [30,31,32,33]. In clinical studies of RCC, CT perfusion has been performed at five- and 10-week time points after initiating treatment, but we are the first to demonstrate that changes can be detected as early as eight days after treatment; however, whether early changes can reliably predict clinical outcome will need to be validated in a larger study.…”
Section: Discussionsupporting
confidence: 85%
“…We observed that early changes in BF and BV in advanced RCC patients were of greater magnitude in patients with stable disease compared to progressive disease. While we were unable to demonstrate statistical significance, our result is consistent with preclinical data in which successful anti-angiogenic treatment has been shown to inhibit VEGFR2, decrease tumor vessel number and density based on immunohistochemistry in xenograft and preclinical models [30,31,32,33]. In clinical studies of RCC, CT perfusion has been performed at five- and 10-week time points after initiating treatment, but we are the first to demonstrate that changes can be detected as early as eight days after treatment; however, whether early changes can reliably predict clinical outcome will need to be validated in a larger study.…”
Section: Discussionsupporting
confidence: 85%
“…However, PET is not generally covered by insurance (only 7 patients in the current study received PET-CT as part of their initial work-up), and our budget did not allow for us to perform the procedure on all patients, and there is the concern of ionizing radiation with repeated CT scanning. We did not compare MRI and CT data, as study has evaluated the value of CT, MRI, and histological examination after cryoablation of renal tumors and concluded that MRI is superior to CT [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prognoses in patients with positive lymph nodes were significantly worse than those with negative lymph nodes. 20,21 In earlier studies, the size of the lymph nodes was used as a positive indicator of lymph node metastasis; however, previous studies have demonstrated that enlarged lymph nodes do not always indicate metastasis and may result from exaggerated inflammatory response, whereas lymph nodes of normal size can also have micrometastases. 22 Therefore, the size of lymph nodes is not the standard to distinguish benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%